El Hombre Feliz . The Happy Man - Gil, Lucina (Gil, Lucina, 2007)
Verzio FF submission The sound of a 24 hour news station broadcast reporting its usual program of international crises and economic downturns provides an insightful foil to Lucina Gil's The Happy Man, a tongue in cheek biography on a self-described "happy man" whose credentials are put to a test by a team of skeptical international researchers. As in Libra, the slice-of-life approach suits the film's structure well, reflecting the film's ideals of enduring love and uncomplicated living.